Phylogenetic analysis of selected representatives of the genus Erica based on the genes encoding the DNA-dependent RNA polymerase I - Gomolińska, Angelika Maria; Szczecińska, Monika; Sawicki, Jakub; Krawczyk, Katarzyna; Szkudlarz, Piotr (Biodiversity: Research and Conservation, 2017)
The rpo genes are characterized by rapidly-evolving sequences. They encode subunits of plastid-encoded (PEP) polymerase (rpoA, rpoB, rpoC1 and rpoC2). This polymerase is one of the most important enzymes in the chloroplasts. The primary aim of the research was to study the rate of molecular evolution in the rpo genes and to estimate these genes as phylogenetic markers based on the example of the genus Erica (Ericaceae). The tested rpo genes demonstrated similarities on multiple levels, for example: phylogenetic informativeness, variation level, intragenic mutation rates and the effect of intragenic mutations on the properties of encoded peptides. This study did not confirm that the analyzed rpo genes are reliable markers and may be helpful in understanding phylogenetic relationships between species that belong to the same genus. The rpoC2 gene was found to be a most useful phylogenetic marker in the Erica genus, while rpoC1 was found to be the least promising gene.